TECHNOLOGY AND GEOPOLITICS: A CHALLENGE IN THE DIGITAL AGE - Kunkunrat Kunkunrat (Jurnal Ekonomi, 2022)
Along with rapid advances in technology, shifts in geopolitical paradigms have occurred, giving rise to new challenges that need to be understood and overcome. ICT has shaped and influenced the dynamics of foreign policy, national security and international relations between countries. This research aims to investigate the impact of the integration of information and communication technology (ICT) on geopolitics in the digital era. The research methodology is descriptive qualitative which includes literature analysis, case studies, and interviews with geopolitical experts and related stakeholders. The results of this research highlight the complexity of the impact of technology in global geopolitics. The findings show that technological advances not only provide opportunities for economic progress and digital diplomacy, but also pose serious challenges, such as the threat of cyber attacks and the risk of proliferation of weapons of mass destruction. This research emphasizes the need for rapid response and international cooperation in developing effective regulatory frameworks to manage risks and ensure ethical use of technology. In conclusion, a deep understanding of the geopolitical impact of technology is key to designing relevant and proactive policies in maintaining global security and stability in this digital era.